A nuclear factor binds to the metal regulatory elements of the mouse gene encoding metallothionein-I. - Labbé, S (1991)
The ability of vertebrate metallothionein (MT) genes to be induced by heavy metals is controlled by metal regulatory elements (MREs) present in the promoter in multiple, non-identical copies. The binding specificity of the mouse L-cell nuclear factor(s) that interact with the element MREd of the mouse MT-I gene was analyzed by in vitro footprinting, protein blotting, and UV cross-linking assays. In vitro footprinting analyses revealed that synthetic oligodeoxynucleotides (oligomers) corresponding to the metal regulatory elements MREa, MREb, MREc, MREd and MREe of the mouse MT-I gene, as well as the MRE4 of the human MT-IIA gene and the MREa of the trout MT-B gene, all competed for the nuclear protein species binding to the MREd region of the mouse MT-I gene, the MREe oligomer being the weakest competitor. In addition, protein blotting experiments revealed that a nuclear protein of 108 kDa, termed metal element protein-1 (MEP-1), which specifically binds with high affinity to mouse MREd, binds with different affinities to the other mouse MRE elements, mimicking their relative transcriptional strength in vivo: MREd greater than or equal to MREa = MREc greater than MREb greater than MREe greater than MREf. Similarly, human MRE4 and trout MREa bind to MEP-1. A protein similar in size to MEP-1 was also detected in HeLa-cell nuclear extracts. In UV cross-linking experiments the major protein species, complexed with mouse MREd oligomers, migrated on a denaturating gel with an apparent Mr of 115,000 and was detected using each of the mouse MRE oligomers tested. These results show that a mouse nuclear factor can bind to multiple MREs in mouse, trout, and human MT genes.